Interest of Colchicine for the Treatment of Cystic Fibrosis Patients. Preliminary Report. Issue 1 (1999) - Sermet-Gaudelus, I.; Stoven, V.; Annereau, J. P.; Witko-Sarsat, V.; Reinert, P.; Guyot, M.; Descamps-Latscha, B.; Lallemand, J. Y.; Lenoir, G.
Abstract : Cystic fibrosis (CF) lung disease is characterized by persistent inflammation. Antiinflammatory drugs, such as corticosteroids and ibuprofene, have proved to slow the decline of pulmonary function although their use is limited because of frequent adverse events. We hypothesized that colchicine could be an alternative treatment because of its antiinflammatory properties and upregulatory effect on cystic fibrosis transmembrane regulator (CFTR) closely related proteins. We herein present results obtained in an open study of eight CF children treated with colchicine for at least 6 months. Clinical status was better in all patients and respiratory function tests significantly improved in five. Median duration of antibiotherapy decreased significantly. These preliminary results support our hypothesis of a beneficial effect of colchicine in CF patients and stress the need for a controlled therapeutic trial.